A comparative study of perceptions towards entrepreneurship in India, Poland, and the USA. (1st January 2013) - Glinka, Beata; Thatchenkery, Tojo
The main purpose of our study was to assess the perceptions of MBA and MS (in organisation development and knowledge management) students towards entrepreneurship. We were interested in questions such as whether students from the post-socialist Poland or less capitalism friendly India will perceive entrepreneurship the same way students from a free-market oriented culture such as the USA. Using qualitative methods of data collection and thematic analysis we explored the data to bring out underlying and deep rooted assumptions towards business, leadership, and wealth creation. We found that core cultural values impact significantly students' attitudes towards entrepreneurship and business creation.